2008
DOI: 10.3358/shokueishi.49.88
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Acid-based Partial-digestion Method for Selective Determination of Inorganic Arsenic in Hijiki and Application to Soaked Hijiki

Abstract: Because there is a great di#erence between the toxicity of inorganic arsenic (As) and organic As in food, the JECFA has set a PTWI value for inorganic As (iAs) rather than for total As. The di#erence in As toxicity makes it necessary to extract iAs completely from food samples for toxicological analysis, but complete extraction of As from most foods including seaweed has not been achieved to date. We developed a partial-digestion method that uses nitric acid as a solvent in order to extract almost all arsenica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…When exposure to As i is high, a biotransformation limit can be reached and As i is not further transformed but accumulates in the organism . Especially in the hijiki algae (Hizikia fusiformis) high concentrations of As i are reported, ranging from 30 to 117 mg kg –1 dry weight (DW), as sold. ,,, Concentrations of As i are mostly <0.8 mg kg –1 DW in other algae (e.g., nori, wakame, etc. ). , …”
Section: Introductionmentioning
confidence: 99%
“…When exposure to As i is high, a biotransformation limit can be reached and As i is not further transformed but accumulates in the organism . Especially in the hijiki algae (Hizikia fusiformis) high concentrations of As i are reported, ranging from 30 to 117 mg kg –1 dry weight (DW), as sold. ,,, Concentrations of As i are mostly <0.8 mg kg –1 DW in other algae (e.g., nori, wakame, etc. ). , …”
Section: Introductionmentioning
confidence: 99%
“…Gamble et al 32) reported that AsSug 408 and AsSug 482 were degraded to DMA via AsSug 328 in a basic environment. In acidic conditions, the formation of AsSug 254 26) and an increase in DMA with heating 33) were also reported. Both of our Boso hijiki products (#6 and #7) contained DMA at the concentration of 0.8 µg/kg dw hijiki, while the DMA levels in two raw hijiki samples (#8 and #9) were much lower (0.2 µg/kg dw hijiki), and these changes in DMA amount may be enhanced by heating.…”
Section: Discussionmentioning
confidence: 99%
“…Since the soaking method used for hijiki samples in the MAFF investigation was not published, it is possible that differences in the soaking process could be the reason. Soaking significantly reduces the iAs content of hijiki [ 12 ]. It may be more appropriate to use our measured hijiki iAs concentration for estimation because the soaking method employed in the present study [ 12 ] was close to that used in general households in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…An additional 31 hijiki samples were purchased in Kanto District, Japan and were prepared for iAs analysis in our laboratory. The hijiki, sold in dried form, was soaked in 40 times its volume of purified water (e.g., 5 g in 200 mL) for 30 min, after which the water was discarded [ 12 ]. The soaked sample was then rinsed twice with 40 times its volume of purified water.…”
Section: Methodsmentioning
confidence: 99%